Agro-Morphological and Cytogenetic Characterization of Colchicine-Induced Tetraploid Plants of Polemonium caeruleum L. (Polemoniaceae) - Tatiana E. Samatadze; Olga Yu. Yurkevich; Firdaus M. Khazieva; Irina V. Basalaeva; Elena A. Konyaeva; Alla E. Burova; Svyatoslav A. Zoshchuk; Alexander I. Morozov; Alexandra V. Amosova; Olga V. Muravenko (Plants, 2022)
Polemonium caeruleum L. (Polemoniaceae) is a valuable medicinal herb with a wide spectrum of biological activities. Under natural conditions, the productivity of this species is rather low. In this study, colchicine-induced tetraploid plants (2n = 4x = 36) of P. caeruleum were obtained, and for the first time, their morphological and cytogenetic characterization was performed. In the tetraploid plants, raw material productivity and also the content of triterpene saponins were significantly higher than in the control diploids. The analysis of chromosome behavior at meiosis and FISH chromosome mapping of 45S and 5S rDNA generally demonstrated stability of both genomes in the tetraploid plants. Based on chromosome morphology and distribution patterns of the studied molecular cytogenetic markers, all chromosome pairs in karyotypes were identified, and chromosome karyograms and idiograms of P. caeruleum were constructed. The revealed specific microdiagnostic characteristics of P. caeruleum (strongly sinuous cells and anomocytic stomata of the leaf epidermis, and also glandular hairs along the veins) could be useful for raw material identification. In the obtained tetraploids, the predominance of large stomata on the lower leaf epidermis was determined. The studied tetraploids can be used in various breeding programs to obtain high-quality pharmaceutical raw materials of P. caeruleum.